Resilienz, Kohärenz und Stresserleben in Familien intellektuell behinderter Kinder - Aschenbrenner, Regina; Doege, Daniela; Holtz, Karl Ludwig; Nassal, Angela; Retzlaff, Rüdiger (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2011)
Abstract Resilience, Coherence and Stress in Families of Children with Intellectual Disabilities This study addresses factors accounting for resilience in the face of adversity and ongoing stress in families of children with intellectual disabilities. 327 families were examined. Measures of family sense of coherence (FSOC), family functioning, stress and coping behaviors were administered. Additionally, measures of the children's level of practical, cognitive and social competencies, as well as problem behaviors were applied. Structural equation modeling was used to examine the relationship between FSOC, family functioning and children's competencies on the one side and parental stress on the other side. Results showed that for the parental couples, as well as for the mothers when regarded separately, FSOC and level of children's competencies were significant predictors of stress. For the fathers, family functioning was a better predictor of stress than family coherence. In order to identify differential indications for counseling practice, moderating effects of family structure, sex and level of the children's competencies were examined. Children's level of practical, social and cognitive competencies emerged as moderator of the relation between stress and family functioning or intensifying of the parents' relationship as a coping behavior. This study demonstrates the significance of family-related variables in the adaptation to living with a child with an intellectual disability.